To investigate the affiliation of XRCC-1 Gene Arg194Trp polymorphism in alcohol and tobacco substance users and loco-regionally progressed Laryngeal squamous cell carcinoma - Raturi Vijay Parshuram; Rajendra Kumar; Madan Lal Brahma Bhatt; Rahul Singh; Devendra Parmar; Jalaj Gaur; Dewesh Kishan; Mandira Saha; Roopali; Pranay Katepogu; Prasad Senthamizh; Tridiv Katiyar (Journal of Oral Biology and Craniofacial Research)
Objectives: The correlation of XRCC-1 Gene Arg194Trp polymorphism with alcohol and tobacco substance user and with loco-regionally progressed squamous cell cancer of the larynx (LSCC) was assessed in this research study. The result of this research study is described herein. Material and methods: A tertiary hospital-based observational case-control research was carried out. DNA segregation and Genotype examination were done from the blood sample of the control group and cases to know the correlation between XRCC-1 gene polymorphism with loco-regionally progressed LSCC and with hazard factors tobacco and alcohol. Results: In the cases, the existence of DNA repair XRCC-1 gene polymorphic variants (Hetero CT and Mutant TT) was recognizable in contrary to the control group arm. The XRCC-1 gene polymorphic hetero (CT) genotype (O.R-1.96; 95% C.I: 1.23–3.13; P < 0.004) and mutant (TT) genotype variants (O.R-1.95; 95% C.I: 0.59–6.44; P = 0.27) was correlated with access hazard of loco-regionally progressed LSCC, and its statistically convincing for polymorphic hetero (CT) variant. The data were adapted for the age of the patients and control group, circadian alcohol intake, tobacco chewing habits, and the tobacco smoking habits during application of multivariate logistic regression. Its apparent that the hazard is amalgamated with hetero (CT) genotype variant (O.R- 1.67; 95% C.I: 0.98–2.82; P = 0.05) and mutant (TT) genotype variant (O.R- 1.62; 95% C.I: 0.88–2.78; P = 0.11) and its statistically convincing for polymorphic hetero (CT) genotype variant. Cases with the record of substance use (alcohol and tobacco) have an abundance of XRCC-1 hetero (CT) and mutant (TT) genotype variants in allegory to control group. Increased hazard is related with XRCC-1 hetero (CT) variant in smokers (O.R 3.28; 95% C.I: 1.45–7.41; P = 0.004), in tobacco chewers (O.R-3.79; 95% C.I: 1.87–7.71; P = 0.0002), and in alcohol consumers (O.R- 4.24; 95% C.I: 2.21–8.15; P= <0.0001) which is statistically significant. Conclusion: This research investigation demonstrates the correlation of XRCC-1 polymorphic hetero genotype (CT) & mutant genotype (TT) variants as hazard factor in loco-regionally progressed LSCC. Cases with the record of alcohol intake habits, tobacco smoking and chewing habits and XRCC-1 hetero genotype (CT) variant have statistically increased the hazard of loco-regionally progressed LSCC, which demonstrate the role of gene-ecological interconnection in modifying the vulnerability of loco-regionally progressed LSCC.